2021
DOI: 10.3390/nano11061429
|View full text |Cite
|
Sign up to set email alerts
|

High-Capacity and Long-Lifespan Aqueous LiV3O8/Zn Battery Using Zn/Li Hybrid Electrolyte

Abstract: Aqueous zinc-ion batteries (AZIBs) are promising candidates for large-scale energy storage because of their low cost and high safety. However, their practical applications are impeded by low energy density and short service life. Here, an aqueous Zn2+/Li+ hybrid-ion battery is fabricated using the LiV3O8 nanorods as the cathode, metallic Zn as the anode, and 3 M Zn(OTf)2 + 0.5 M LiOTf aqueous solution as the electrolyte. Compared with the batteries using pure 3 M Zn(OTf)2 electrolyte, the cycle performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…However, the Al 2p peak was shifted to the low binding energy from 77.0 eV for Al−O (Al 2 O 3 ) to 75.9 eV for Al−OH (Al(OH) 3 ), and the XPS Zn 2p spectrum further showed two shifted binding energies of oxidation states from 1022.7 and 1045.9 eV for Zn−O (ZnO) to 1023.3 and 1046.4 eV for Zn−OH (Zn(OH) 2 ) during the deintercalation process. It means that the Al and Zn remained in a triflate formation (OTF) with layered hydroxides (LDHs) in the cathode, such as (Al x (OTF) y (OH) 2x‐y nH 2 O and Zn x (OTF) y (OH) 2x‐y nH 2 O) [51,52] . This result confirmed that the Al and Zn ions exhibited a negligible change in their oxidation states during the charging and discharging reaction, which strongly corresponds to the electrochemical performance described in Section 3.2.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…However, the Al 2p peak was shifted to the low binding energy from 77.0 eV for Al−O (Al 2 O 3 ) to 75.9 eV for Al−OH (Al(OH) 3 ), and the XPS Zn 2p spectrum further showed two shifted binding energies of oxidation states from 1022.7 and 1045.9 eV for Zn−O (ZnO) to 1023.3 and 1046.4 eV for Zn−OH (Zn(OH) 2 ) during the deintercalation process. It means that the Al and Zn remained in a triflate formation (OTF) with layered hydroxides (LDHs) in the cathode, such as (Al x (OTF) y (OH) 2x‐y nH 2 O and Zn x (OTF) y (OH) 2x‐y nH 2 O) [51,52] . This result confirmed that the Al and Zn ions exhibited a negligible change in their oxidation states during the charging and discharging reaction, which strongly corresponds to the electrochemical performance described in Section 3.2.…”
Section: Resultssupporting
confidence: 69%
“…Accordingly, the peak intensities of Al 2p and Zn 2p increased after intercalation (Figure 4c ). [51,52] This result confirmed that the Al and Zn ions exhibited a negligible change in their oxidation states during the charging and discharging reaction, which strongly corresponds to the electrochemical performance described in Section 3.2. Consequently, Al and Zn ions are expected to affect the (de)intercalation process on the cathode, resulting in an enhanced capacity in AAIBs.…”
Section: Electrochemical Study Of Zn-al/3 M Al(otf) 3 /V 6 O 13 Aaibssupporting
confidence: 79%
“…The research of cathode materials for ZIBs has generated a lot of debate since it is crucial to the operation voltage, cycle stability, and rate performance. Vanadium-based materials have attracted increasing attention as cathode materials for the second energy storage system because of their high specific capacity (>300 mAh g –1 ), multivalent states of vanadium, and unique properties of REDOX processes. , Many vanadium-based materials, including V 2 O 5 , M x V 2 O 5 , H 2 V 3 O 8 , VS 2 , LiV 3 O 8 , Na 0.33 V 2 O 5 , , and Mg x V 2 O 5 , have been developed for ZIB cathodes. Ammonium vanadate with a wide layer spacing outperforms other vanadium-based materials in terms of electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been growing calls from various industries to improve battery safety, mainly due to concerns about the fire and even explosion risks of lithium-ion batteries [ 1 , 2 , 3 ]. Therefore, it is very important to develop alternative high-performance batteries with lower cost and naturally non-explosive properties [ 4 ]. Rechargeable aqueous zinc-ion batteries (AZIBs) have recently attracted much attention due to their numerous advantages, especially their excellent safety [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%